Kepribadian Konselor dalam Perspektif Islam - Marta Suhendra (Fakultas Tarbiyah dan Keguruan UIN Imam Bonjol Padang, 2016)
Counseling in Islam is a comprehensive concept for life. The concept that can help happiness, tranquility and contentment for humans. The concept is capable of directing man towards the best path, the path of self actualization to deliver a perfect human being. Achieve it all counselors need to equip themselves to have at least four competencies in themselves, such as: 1) pedagogic competence, 2) personal competence, 3) social competences and 4) professional competence. Personal competence special attention in the Islamic counseling. This is because in Islam counseling counselor's personality will become a role model for students who will be guiding learners in actualize himself.